Surface tension and density of the binary mixtures toluene + methyl propanoate, toluene + methyl pentanoate, toluene + methyl heptanoate and toluene + methyl octanoate at atmospheric pressure and 288.15, 298.15 and 308.15 K - Mussari, Lelia María Ester (2017)
Surface tension and density were measured for the binary mixtures toluene  +  methyl propanoate, toluene  +  methyl pentanoate, toluene  +  methyl heptanoate and toluene  +  methyl octanoate at atmospheric pressure and 288.15, 298.15 and 308.15 K. Meditions were done using mechanical oscillation densimetry and falling drop tensiometry. Densities and surface tensions increases as it grows the carbonated chain of the methyl esters and decreases as temperature increases. Experimental data were satisfactory ﬁtted by the polynomial equation of Redlich-Kister. Adsorption isotherm of Gibbs was applied to estimate the relative adsorption of each ester respect to toluene. The modiﬁed group contribution model of UNIFAC was using to estimate the activity coeﬃcients of the components. Positive values of the relative adsorption showed that there was a great accumulation of ester molecules on the surface of the dissolution respect to the ﬂuid?s sine.